Model Penyusunan Rancangan Peraturan Daerah Berbasis Partisipatif - Diyanto, Aris, Prof. Dr. Harun, SH., M.Hun, Dr. Aidul Fitriciada Azhari, SH., M.Hum (2016)
Local regulations are a manifestation of the democratic outcome, because it is made by a body set up by the people, namely the regional parliament. But the fact in mechanism regulation making does not give space to the people to hang out in the aspiration, or no pattern to obtain data about the problem of the original community. It would require a new pattern or model of public participation system. It draws on a juridical empirical research, with qualitative analysis. source material in the form of legal regulation, books and journals, mass media, the primary ingredient in the form of interviews with key respondents. This paper described the results of the study, the area formed a research institute intensive excavation information, issues and conduct kuanitatif calculation and qualitative analysis. The work of this institution become a source of data for policy making (local laws) either by the Regional Parliament or mayor